Pola Komunikasi Antar Budaya Suku Batak dan Jawa di Lingkungan II Untemanis Kelurahan Losung Batu, Padangsidimpuan, Sumatera Utara - Vina Safitri; Muhammad Firdaus (Lembaga Pengembangan Kinerja Dosen, 2023)
Communication becomes very important in people's lives, because with indirect communication we can understand the attitudes, behaviors and actions of the environment around us. Communication that occurs between the Batak and Javanese tribes that occurs is called intercultural communication which involves two or more people with different cultural backgrounds. Communication and interaction between Batak and Javanese tribes in Environment II Untemanis is intertwined with the process of understanding each other's differences. This study is intended to determine the pattern of intercultural communication between Batak and Javanese tribes in Environment II Untemanis, Losung Batu Village, North Padangsidimpuan District, Padangsidimpuan Regency, North Sumatra. This research uses qualitative methods with a descriptive approach. The subjects in this study amounted to 14 informants determined purposively, consisting of the head of ligkungan II Untemanis, traditional leaders / hatobangon, and Batak and Javanese people who were at least domiciled for 3-4 years. Data collection is carried out by interview, observation and documentation techniques. In analyzing data, this study uses data reduction, data presentation and conclusions. The results of this study show that communities in Environment II Untemanis coexist harmoniously through a process of adjustment and then accept each other's differences. In the process of communication and interaction these two tribes use mixed languages, namely Batak, Javanese and Indonesian. Despite having different cultural backgrounds, Batak and Javanese people in this environment live without any discrimination. The existence of high tolerance in Environment II Untemanis makes community life harmonious and open to each other. The pattern of communication that occurs between the Batak and Javanese tribes in this environment is a circular pattern. The creation of a circular pattern that indicates a reciprocal process due to supporting factors, namely the ability to communicate, mutual acceptance and respect between cultures, and the adaptability of the Batak and Javanese people.